2018
DOI: 10.1155/2018/8207098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extrapulmonary Tuberculosis Using Gene Xpert MTB/RIF Assay and Fluorescent Microscopy and Its Risk Factors at Dessie Referral Hospital, Northeast Ethiopia

Abstract: Background Tuberculosis is a major public health problem and extrapulmonary tuberculosis (EPTB) accounts for a significant proportion of tuberculosis cases worldwide. Objective To determine the magnitude of EPTB, associated risk factors, and agreement of diagnostic techniques at Dessie Referral Hospital. Methods A cross-sectional study was conducted on consecutive presumptive EPTB cases from March 1 to June 30, 2017. Sociodemographic characteristics and other variables were collected using a structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
2
16
1
1
Order By: Relevance
“…Among 100 RR-TB results, majority (62%) were detected from sputum samples, while the remaining 38 samples were detected from deferent types of extra pulmonary samples. Among the extra pulmonary samples, half were a lymph node aspirate sample which is similar with the study reported from Dessie, Ethiopia (11). In this review higher DNA amount (high or medium) was observed in the sputum samples, while lower DNA amount (low or very low) was observed in extra pulmonary samples.…”
Section: Discussionsupporting
confidence: 87%
“…Among 100 RR-TB results, majority (62%) were detected from sputum samples, while the remaining 38 samples were detected from deferent types of extra pulmonary samples. Among the extra pulmonary samples, half were a lymph node aspirate sample which is similar with the study reported from Dessie, Ethiopia (11). In this review higher DNA amount (high or medium) was observed in the sputum samples, while lower DNA amount (low or very low) was observed in extra pulmonary samples.…”
Section: Discussionsupporting
confidence: 87%
“…Among 100 RR-TB results, the majority (62) was detected from sputum samples, while the remaining 38 samples were detected from different types of extrapulmonary samples. From the extrapulmonary samples, half was a lymph node aspirate sample which is similar to the study reported from Dessie, Ethiopia [14]. In this review higher DNA amount (high or medium) was observed in the sputum samples, while lower DNA amount (low or very low) was observed in extrapulmonary samples.…”
Section: Discussionsupporting
confidence: 83%
“…The national TB programs, however, have focused on PTB because of transmissibility, and likewise, the majority of studies done in Ethiopia focused on PTB [9]. Some of the previously conducted studies in Ethiopia focused on the genotypic characterization of mycobacterium causing EPTB [8,[10][11][12] and other assessed diagnostic modalities accuracy and sensitivity for lymph nodes TB [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A detailed characterization incorporating sociodemographic, clinical, laboratory, and radiological features of adult EPTB cases is lacking in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%